2023
DOI: 10.1177/07482337231156284
|View full text |Cite
|
Sign up to set email alerts
|

Association between bisphenol A exposure and thyroid dysfunction in adults: a systematic review and meta-analysis

Abstract: The occurrence of thyroid dysfunction is affected by environmental factors, and BPA is a ubiquitous environmental pollutant with the potential to cause thyroid dysfunction. However, the limited epidemiological evidence shows an inconsistent association between BPA exposure and thyroid dysfunction. Therefore, the literature on the impact of BPA on thyroid was sorted and analyzed to study the relationship between BPA and adult thyroid function. The studies published on or before 23rd May 2022 from PubMed, Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Furthermore, this study observed a correlation between urinary BPA and FT4 levels (r=0.29, P < 0.05), which aligns with findings in previous research. A systematic review and meta-analysis ( 14 ) on BPA exposure and thyroid dysfunction in adults revealed a positive correlation between BPA concentration and FT4 in females, and the pooled correlation coefficient was 0.006 (95%CI = 0.003-0.008). Nonetheless, there are studies that deviate from the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study observed a correlation between urinary BPA and FT4 levels (r=0.29, P < 0.05), which aligns with findings in previous research. A systematic review and meta-analysis ( 14 ) on BPA exposure and thyroid dysfunction in adults revealed a positive correlation between BPA concentration and FT4 in females, and the pooled correlation coefficient was 0.006 (95%CI = 0.003-0.008). Nonetheless, there are studies that deviate from the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The process of deiodination, facilitated by the enzyme deiodinase (DIO1), plays a fundamental role in regulating the concentration of thyroid hormones in peripheral tissues and plasma [ 99 , 100 ]. Although there are numerous contaminants known to disrupt the action of thyroid hormones [ 101 , 102 , 103 ], the mechanisms behind these disruptions are only partially understood, resulting in a gap in current methods for detecting such chemicals.…”
Section: Need For New Methodsmentioning
confidence: 99%